2012
DOI: 10.1155/2012/124703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yoga Interventions on Fatigue: A Meta-Analysis

Abstract: Background. Researchers aimed at systematically reviewing and meta-analyzing the effectiveness of yoga interventions for fatigue. Methods. PubMed/Medline was searched until January 2012 for controlled clinical studies. Two reviewers independently extracted the data. The methodological quality of the studies was assessed. A meta-analysis was performed. Results. Nineteen clinical studies (total n = 948) were included in this review. Investigated yoga styles included Hatha, Iyengar, Asanas, Patanjali, Sahaja, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 48 publications
1
30
0
6
Order By: Relevance
“…This result is similar to a meta-analysis of 19 RCTs on yoga therapy in patients with fatigue, which showed only a small effect [24]. The studies reviewed included not only cancer patients but also patients with fibromyalgia, chronic pancreatitis, multiple sclerosis, asthma, and dialysis.…”
Section: Discussionsupporting
confidence: 82%
“…This result is similar to a meta-analysis of 19 RCTs on yoga therapy in patients with fatigue, which showed only a small effect [24]. The studies reviewed included not only cancer patients but also patients with fibromyalgia, chronic pancreatitis, multiple sclerosis, asthma, and dialysis.…”
Section: Discussionsupporting
confidence: 82%
“…36 Yoga is classified as a form of CAM by the National Institutes of Health; the practice of yoga integrates the physical, mental, and spiritual components of an individual in order to improve health and well-being. 36 The past decade of research has demonstrated a variety of therapeutic benefits associated with the practice of yoga in treating many illnesses, chronic diseases, and disabilities, such as chronic pain, 36 high blood pressure, 37 autism spectrum disorder, 38 trauma, 39 Alzheimer's disease, epilepsy, fibromyalgia, peripheral nervous system disorders, 10 fatigue and mood, 40,41 chronic insomnia, 42 depression, 43 heart attack and stroke, 36 and eating disorders, 44 as well as improved quality of life, 41 neuromuscular function, 45 flexibility, 46 and better physical, emotional, and spiritual wellness among patients with cancer. 47 For example, Carson and colleagues 47 looked at the effects of a novel yoga intervention-the Yoga Awareness Program-among 13 women with metastatic breast cancer.…”
Section: Therapeutic Yogamentioning
confidence: 99%
“…In gleicher Weise kann auch der Einsatz von Yoga und Meditation gesehen werden, wodurch die konstruktive Auseinandersetzung mit der Krebserkrankung möglich wird [28,29,30,31]. Die differenzierten Massagetechniken mit ausgewählten medizinierten Ölen bewirken, synergistisch zu den letztgenannten Maßnahmen, eine Stabilisierung der Gesamtpersönlichkeit sowie eine wirkungsvolle Dämpfung des aggravierten vata-Prinzips, das für die krankheitsbedingte Desintegration und auf der somatischen Ebene für die Metastasierung verantwortlich zu machen ist.…”
Section: Diskussionunclassified